Omniscient reader's viewpoint. 06 - Umi (Korean author at Redice Studio); Singsyong; Torres, J., 1969- (Ize Press, 2025)
Having sole knowledge of the story has allowed Dokja to stay one step ahead in the cruel new world...but what if that's no longer the case? With the appearance of the mysterious group calling themselves "the Oracles" he must now contend with other readers! And all the while, moving behind the scenes is a shadowy mastermind whose knowledge of TWSA seems to match Dokja's own...?--